Slang Language Subtitle Strategy in the Movie Entitled “The Social Network” - Lilik Istiqomah; Anisa Nur Rohimah; Azizah Widya Pratiwi (Langkawi: Journal of The Association for Arabic and English, 2019)
This paper focuses on the analysis of translation strategies of slang language as employed in the movie entitled “The Social Network”. This paper analyzes the translation strategies of the slang language from English into Indonesia from the movie entitled “The Social Network”. Baker’s translation strategies were used in this paper in order to analyze the data of this paper.  The study findings reveal that there are 30 slang words used in this movie, and the subtitler adopted five translation strategies by Baker for translating the slang words in this movie. The analysis also reveals that most of the slang words in the movie have related words with the target language. There are no English slang words that were translated into Indonesia slang words in the movie. The subtitler mostly used the strategies for translating the English slang words into Indonesian words that have a similar expressive meaning. It can be interpreted as a result of the different culture of both countries that makes different slang words.